The Criminal Liability of Bank-Affiliated Notaries for the Confidentiality Principle of Banks in Connection with Deposit Collateral Agreements - Weminto Suryadi; Fauzie Yusuf Hasibuan; Lilik Mulyadi; Yuhelson; Januar Agung Saputera (GoAcademica Research & Publishing, 2023)
This research focuses on the criminal liability of notaries affiliated with banking institutions for the guarantee binding act in the form of a deposit connected to the principle of bank secrecy in Indonesia. Through the analysis of relevant laws, including Bank Indonesia Regulation No. 2 of 2000, Notary Position Law, and Bank Confidentiality Law, the study aims to answer two research questions: the form of criminal liability of notaries affiliated with banking institutions for the guarantee binding act and the ideal concept of criminal liability. The findings suggest that notaries who breach the principle of bank secrecy can face criminal charges, and the ideal concept of criminal liability should balance the interests of customers and banking institutions while maintaining bank secrecy and customer privacy. The study's implications call for clear guidelines and regulations for notaries' responsibilities in guaranteeing binding acts related to deposits and penalties for notaries who violate the principle of bank secrecy.